The Earnings and Employment Losses Before Entering the Disability System - María Cervini-Plá; Judit Vall-Castello (Institute for the Study of Labor (IZA), 2015)
Although a number of papers in the literature have shown the employment and wage differences between disabled and non-disabled individuals, not much is known about the potential employment and wage losses that disabled individuals suffer before being officially accepted into the disability insurance system (DI). Therefore, in this paper we distinguish between individuals that enter the DI system due to a working accident (sudden health shock) and individuals that become disabled due to an ordinary illness to identify the differences in employment and wages between these two groups before they are officially accepted into the DI system. We combine matching models and difference-in-difference and we find that the wage (employment) growth patterns of both groups of workers become significantly different three (six) years before entering the DI system. More specifically, our estimates suggest that one year before entering the system, there is a difference of 27 Euros/month in the wages of the two groups (3% of average wage) as well as a 10 percentage point difference in employment probabilities.
Keywords: J31; I13; 330; disability system; employment; wage loss